1990
DOI: 10.1002/mrd.1080250305
|View full text |Cite
|
Sign up to set email alerts
|

Male accessory sex glands produce heparin‐binding proteins that bind to cauda epididymal spermatozoa and are testosterone dependent

Abstract: Heparin binds to bovine sperm and stimulates capacitation in vitro. Seminal plasma alters the ability of epididymal sperm to bind heparin, and several heparin-binding proteins (HBPs) have been identified in bull seminal plasma. This study had three objectives: 1) to identify production sites of seminal plasma HBPs, 2) to determine which HBPs bound to cauda epididymal sperm, and 3) to determine whether presence of HBPs was testosterone dependent. Proteins from bull or rat seminal vesicles, prostates, and bulbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 32 publications
0
39
0
3
Order By: Relevance
“…Sperm proteins were extracted as per the method described by Nass et al (1990) with slight modifications. The sperm pellets were thawed to room temperature and washed twice with 1 ml of TC buffer at 5°C.…”
Section: Extraction Of Seminal Plasma and Sperm Proteinsmentioning
confidence: 99%
“…Sperm proteins were extracted as per the method described by Nass et al (1990) with slight modifications. The sperm pellets were thawed to room temperature and washed twice with 1 ml of TC buffer at 5°C.…”
Section: Extraction Of Seminal Plasma and Sperm Proteinsmentioning
confidence: 99%
“…These heparin-binding proteins were divided into three families of proteins having molecular weights of 14-18, 24, and 31 kDa, but it is not known whether these proteins are related to each other. They are mainly products of the seminal vesicles and their production is testosterone dependent (Nass et al, 1989). The 14 to 18-kDa proteins are similar in molecular weight to fibronectin-like polypeptides which are major components of bovine seminal plasma (Esch et al, 1983;Baker, 1985;Majunath and Sairam, 1987;Seidah et al, 1987).…”
Section: Effect Of Seminal Plasma On the Interaction Ofmentioning
confidence: 99%
“…Other studies have shown that accessory glands produced and secreted HBP into seminal fluid , and HBP bound to sperm at ejaculation (Miller et al, 1990;Nass et al, 1990). Miller et al (1990) reported that HBP constituted 28% of the protein component of seminal fluid or approximately 19.6 mg HBP/mL of ejaculate, and HBP-B5 constituted 6% of the total HBP in fluid from vasectomized bulls.…”
Section: Heparin Binding Proteins (Hbps)mentioning
confidence: 98%
“…Sperm from high-fertility bulls have a greater frequency of acrosome reactions in response to heparin-like material (Lenz et al, 1988). Heparin-binding proteins (HBPs) are produced by the male accessory glands, secreted into seminal fluid (Nass et al, 1990). Fertility for Group 1 (HBP-B5) in sperm membranes but undetectable HBP-B5 in seminal fluid) was 82% of 1,692 cows.…”
Section: Heparin Binding Proteins (Hbps)mentioning
confidence: 99%